Poświęcić niepewność – prolegomena do badań nad kinem postsekularnym - Piskorska , Anna Maria (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2021)
This article undertakes the issue of defining film phenomena which put forward questions of a primary religious nature (about the meaning of life, source of evil, life after death, the existence of Absolute, etc.) in a way that is independent from major religious traditions. The author posits that describing this phenomenon in the case of European film culture is done best by employing the philosophical thought of postsecularism. Utilizing Mieke Bal’s method of cultural analysis, the author takes as an example the term “sacrifice” to point to the existence of different models by which religious topics are undertaken by the cinema. This leads to a preliminary typology of the phenomenon which differentiates between ‘apologetic’ and ‘critical’ films and, furthermore, between films that refer to particular religious traditions and those expressing a postsecular perspective.